Maternidade real: uma fórmula discursiva? - Zago, Vanessa Koenigstein (2021)
As the fourth wave of the feminist movement advances, social networks have been working as a platform for the problematization of a series of minorities questions; among them, one centered in the motherhood function, till now seen under a socio-historical idealization of the mother figure. As opposed to this optimal construction comes the “real motherhood” syntagma as a type of “movement,” reaching visibility within and outside the networks it originally appeared. In this context, the core objective of the research is to understand if the “real motherhood” syntagma could be elevated to the status of discursive formula, anchoring for this purpose in the “formula” notion from the Discourse Analysis, as a theoretical and methodological proposal by Alice Krieg-Planque. Thus, the study is feasible by taking as analysis criteria the four properties inherent to the formula: (1) its crystallization, through a moderately stable signifier, (ii) its inscription in a discursive dimension, (iii) the fact that, as a social referent, it has a meaning for everybody at a given time, and (iv) its controversial nature, bearing socio-political issues. Complementarily, we resort to the studies undertaken by Dominique Maingueneau about topics and non-topics units, as well as to the inter-discourse principle. Also, as more specific theoretical contributions, there is the Idealized Cognitive Model, from George Lakoff, and the notion of digital-native discourse, as per Marie-Anne Paveau. The corpus for the analysis is composed of 61 digital texts extracted from various online media using specific criteria, as the syntagma "real motherhood" (and not "#realmotherhood") and the definition of a starting date for tracking its history, that was 2010 when the internet access in Brazil was expanded. The sample covers the range between 2011- 2021, since the identification of the first record of "real motherhood" on the internet, up to the statements put into circulation more recently, due to the actuality of the theme at the pandemic and the discussions associated to the intensification of the maternal burden in this period. Even considering Krieg-Planque's assumption that the formula is a gradual category, it was noted in the study that "real motherhood" has the potential to be elevated to the formula status, as the neologism fills broadly one of the formula's four properties, having a crystallized sequence. The other three dimensions are still in the formation stage. On the discursive, "real motherhood" dialogues mainly with the maternity, but also participates actively in discussing questions around the problematization of this theme, mainly on the web. In the social referent, it does not circulate in the broad public space, and it is limited to a specific domain. Still, in the face of contemporary media fragmentation, one must consider that the assessment of what is public space is under questioning. Although the consequence of this greater reverberation in his discursive community weakens his possibilities of generating great controversy within his environment, there are facets of polemicism. Two hypotheses could be made in the face of the fluidity of these three proprieties: the first one seems to originate from a symptom of the naturalized way that the Brazilian society deals with maternity – as an already established theme and on which there would be no room for problematization. The second seems to be linked to the public space notion and publicization – the major communication vehicles are still the most important vectors for the promotion, magnification, and circulation of formulas. In conclusion, it is possible to say that the study allowed not only to verify the formulaic potential of "real motherhood" but also to unveil the power relations and opinion of contemporary Brazilian society on the issue of maternity